The Peculiarities of Development of Farming Culture in Central Asia. - Erkinovna, Yunusova Khurshida; Boymakhmatovich, Kholikulov Akhmadjon; Abdumavlyanovich, Usarov Umidjan; Ortikovna, Akramova Fazilat (International Journal of Psychosocial Rehabilitation, 2020)
In Central Asia, where the climate is extremely mild and droughty, with hot summers, no clouds, and the winter is cold and frost-free, agriculture has a long history. The local people have extensive experience in crop rotation, using the land effectively, planting crops such as wheat, barley, rice, sorghum, cotton, legumes and vegetables, up to four times a year. With spring’s arrival in February, farming began in March in the south of the region and in April in the north. The rapid melting of snow and the warming of the ground by March also allowed high yields to plow and prepare for farming. In the spring, it was raining more than autumn and lasting until May. In recent months, the rainy season has begun with low rainfall. Among crops, wheat and barley are sown with cereals on dry land. On irrigated lands rice, corn, millet, legumes (moss, beans) are planted. In addition, there is growing horticulture and viticulture, planting vegetables and melons. The alfalfa and other feed crops needed for livestock are also planted too much. Farmers pay special attention to the damaging factors. They knew that the strong wind and the gale were very windy, and they planted cotton that was well watered and not affected by the wind. They have planted more trees to maintain regular land reclamation. In Central Asia, based on irrigated agriculture, the local population has been using water efficiently. Farmers used their own "traditional" methods to pump water through irrigation canals and irrigation ditches, and built irrigation systems from ancient times, and they built fast and inexpensive irrigation systems using simple materials such as soil, turf, stone, horns. Syrdarya, Amudarya, Chirchik, Naryn, Karadarya, Akhangaran, Zarafshan, Kashkadarya.